1998
DOI: 10.1046/j.1365-2648.1998.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and autonomy of Hong Kong registered nurses

Abstract: This research examines job satisfaction and need for autonomy of 190 registered nurses in Hong Kong using a cross-sectional survey design. The level of job satisfaction towards six job components (autonomy, professional status, pay, interaction, task requirements and organizational policies) was measured using the Index of Work Satisfaction. Results showed that the sample was dissatisfied more than satisfied, they valued the job components of autonomy, professional status and pay more than interaction, task re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
54
2
20

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 47 publications
(58 reference statements)
10
54
2
20
Order By: Relevance
“…Thus, it is concluded that the management group was satisfied with the work requisites, while the clinical group was less satisfied. This finding is supported in most studies on this component, in which routinization, bureaucratization, inflexibility at work, quantity/burden and care model are causal factors of dissatisfaction (5,(14)(15)(16) . As work requisites are directly related with nursing work conditions and nurses are exposed to occupational risks, stress, among others, the influence of these factors on the clinical group is more enhanced.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, it is concluded that the management group was satisfied with the work requisites, while the clinical group was less satisfied. This finding is supported in most studies on this component, in which routinization, bureaucratization, inflexibility at work, quantity/burden and care model are causal factors of dissatisfaction (5,(14)(15)(16) . As work requisites are directly related with nursing work conditions and nurses are exposed to occupational risks, stress, among others, the influence of these factors on the clinical group is more enhanced.…”
Section: Resultsmentioning
confidence: 62%
“…Finally, the analysis of the assessed six professional satisfaction components' importance revealed the autonomy component as the most important item to enhance satisfaction among professionals (5,15,18) . These findings support the present study results, as the two participant groups also scored the autonomy component as the most important job satisfaction item (Chart 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the nursing literature, several studies have found that wages and salaries impact overall job satisfaction but rarely went a step further to determine the relative importance between job and pay satisfaction in terms of their effects on turnover (Carr and Kazanowski, 1994;Frisina, Murray and Aird, 1988;Fung-kam, 1998;Huey and Hartley, 1988). For instance, Fung-kam (1998) found that the three factors that have the most influence on job satisfaction were autonomy, professional status, and pay.…”
Section: Pay Satisfaction Job Satisfaction and Turnover Intentmentioning
confidence: 99%
“…For instance, Fung-kam (1998) found that the three factors that have the most influence on job satisfaction were autonomy, professional status, and pay. Many studies do not find pay to be associated with overall job satisfaction among RNs (Butler and Parsons, 1989;Cavanagh, 1992;Reineck and Furino, 2005).…”
Section: Pay Satisfaction Job Satisfaction and Turnover Intentmentioning
confidence: 99%
“…A satisfação no trabalho é considerada um dos indicadores de QVT e sua medida tem sido utilizada em estudos no Brasil e no exterior (8)(9)(10)(11)(12) . Alguns estudos realizados especificamente para avaliar a satisfação no trabalho entre profissionais do Bloco Cirúrgico (BC), em nosso país, foram realizadas com a utilização de diferentes instrumentos para coleta de dados (13)(14)(15) .…”
unclassified